Pasmo Płytowe z Żebrami Jednostronnymi - Ganowicz, R. (Engineering Transactions, 1960)
It is shown that all the mechanical quantities of an isotropic plate strip having ribs on one side may be represented in the form of closed expressions. The solution is obtained with the assumptions and on the basis of the relations obtained by PFLÜGER, [4]. A system of three equations for the displacements u, U, W of a point of the middle surface obtained on the basis of the Ref. [4] is reduced to one equation for the displacement function. Assuming the solution in the form of a trigonometric series, expressions are obtained which can be written in a closed form.A numerical example is given of which the results are confronted with the values obtained from model tests, which are found to be in with the theoretical solution agreement